A case of symptomatic double coronary artery-pulmonary artery fistulae - Patted Suresh; Halkati Prabhu; Dixit M; Patil Ravikant (Wolters Kluwer Medknow Publications, 2010)
A 57-year-old lady presenting with angina was found to have multiple coronary arterio venous fistulae (CAVF) arising from both left and the right coronary arteries and draining into the pulmonary artery. She underwent successful surgical closure of these CAVF.